THE INFLUENCE OF TRANSCENDENTAL VALUE AS AN EFFORT OF ONLINE TRANSACTION LEGAL PROTECTION IN THE ERA OF DIGITAL ECONOMY - Rizka Rizka (Universitas Muhammadiyah Ponorogo, 2019)
The digitalization of the economy sector in the industrial revolution 4.0 needs to be approached with a smart attitude so as to not bring loss to both the consumers and the business holders, by transforming the instrument of consumer rights in an updated and a better way. The development of technology has spoiled human beings in all aspects, including in muamalah. like transaction. The society’s rapid consumptive behavior becomes a business opportunity for the investors to invest their capital in the field of trade, which is also rapidly developing. The increasing demand of consumptive products pushes the popularity of online transaction. There exist hundreds of online shops, either official shops or those undergoing transaction through social media. Anyone can be owners of online shops, and the consumers can be adults, teenagers, and even children. This condition causes some problems, such as the misuse of online transaction for deception, offering products which are not the same as the real items, or worse, not sending the products after the consumer has transferred the money. The results show that in online transactions, there are many dishonest sellers who legalize all methods to practice deception, so there needs to be a connection between online transaction and religion with the hope to minimize the chance of harm for both the consumers and the sellers.